2015
DOI: 10.1021/acs.iecr.5b02824
|View full text |Cite
|
Sign up to set email alerts
|

Magnetorheology of Carbonyl Iron Dispersions in 1-Alkyl-3-methylimidazolium Ionic Liquids

Abstract: In this work, a range of ionic liquids (IL), all based in 1-alkyl-3-methylimidazolium, [EMIM] + and [BMIM] + cations, with different anions: [NTf 2 ] -, [CF 3 SO 3 ] -, [SCN] -, [BF 4 ] -, [PF 6 ] -and [CH 3 COO] -were used as carrier fluids to prepare magnetorheological (MR) fluids with 30 vol% of carbonyl iron powder (CIP), grade EW (BASF SE), without additives. IL-MR fluids were characterized in the presence of magnetic fields with conventional steady shear stress ramps, constant shear rate magnetosweeps a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 27 publications
(37 reference statements)
1
6
0
Order By: Relevance
“…/H The second point we need to take into account is that, in the plate-plate configuration, the yield stress provided by the software is overestimated by a factor of 4/3 Laun et al, 2010). The data collected in different publications (Kordonski and Golini, 1999;Chin et al, 2001;Lim et al, 2004;Jang et al, 2005;Cheng et al, 2009;Ierardi and Bombard, 2009;Laun et al, 2010;Kim et al, 2012;Bombard et al, 2015;Esmaeilnezhad et al, 2017;Dong et al, 2018;Plachy et al, 2018) are reported in Table S1 and plotted in Figure 1B (blue diamonds). There is a considerable scatter of the data, but it appears clearly that the affine model with the calculation of forces through FEM (red curve), provides the best prediction compared to both Equation (6) and Equation (7).…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…/H The second point we need to take into account is that, in the plate-plate configuration, the yield stress provided by the software is overestimated by a factor of 4/3 Laun et al, 2010). The data collected in different publications (Kordonski and Golini, 1999;Chin et al, 2001;Lim et al, 2004;Jang et al, 2005;Cheng et al, 2009;Ierardi and Bombard, 2009;Laun et al, 2010;Kim et al, 2012;Bombard et al, 2015;Esmaeilnezhad et al, 2017;Dong et al, 2018;Plachy et al, 2018) are reported in Table S1 and plotted in Figure 1B (blue diamonds). There is a considerable scatter of the data, but it appears clearly that the affine model with the calculation of forces through FEM (red curve), provides the best prediction compared to both Equation (6) and Equation (7).…”
Section: Comparison With Experimentsmentioning
confidence: 99%
“…The traditional method of using surfactants to change the interface will complicate the composition of the rheological fluid, and cannot distinguish its influencing factors and effects well. Although ionic liquids have been used as carrier fluids for MRF (Guerrero-Sanchez et al, 2007;Gómez-Ramírez et al, 2011;Jönkkäri et al, 2014;Bombard et al, 2015), few people have noticed that although its viscosity is similar to that of silicone oil, its surface tension is higher than that of silicone oil. This will bring different interface effects.…”
Section: Introductionmentioning
confidence: 99%
“…Usually, a magnetic composite matrix is regarded as a two-phase conductive material, in which the magnetic particles play a considerable role in contributing to the conductivity. Over the past decades, numerous metals or alloys have been successfully developed. , Among them, soft micron carbonyl iron (CI) particles are highly desirable because of their high saturation magnetization and common availability. , On the application of a magnetic field, the micron CI particles distributed in the nonmagnetic matrix become polarized and gather in chain or cluster structures owing to dipole interactions. To meet the requirements of dispersion ability and MR properties, various modification methods have been successively performed including surface coatings, magnetic nanoparticles, and additive fillers. In our previous study, bidisperse magnetic microspheres containing micron CI particles and Fe 3 O 4 nanoparticles wrapped in gelatin (GE) and multiwalled carbon nanotubes (MWCNTs) were prepared via a sol–gel method, which showed enhanced MR properties while maintaining the original dispersion stability of CI particles.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Among them, soft micron carbonyl iron (CI) particles are highly desirable because of their high saturation magnetization and common availability. 11,12 On the application of a magnetic field, the micron CI particles distributed in the nonmagnetic matrix become polarized and gather in chain or cluster structures owing to dipole interactions. To meet the requirements of dispersion ability and MR properties, various modification methods have been successively performed including surface coatings, magnetic nanoparticles, and additive fillers.…”
Section: Introductionmentioning
confidence: 99%